Can apples be used as a source of fermentable carbohydrate when making alfalfa silage? - Güler, T; Çerçi, IH; Çiftçi, M; Ertas, ON (Ecole Nationale Veterinaire Toulouse, 2006)
The aim of the current experiment was to explore the possibility of substituting barley grain or sucrose. which are traditionally used its carbohydrate sources in silage making. with inedible apples (unfit for human Consumption). Alfalfa silages were made with the following additives : control group (no additive), S-1 group with 1% Sucrose, S-2 group with 2% sucrose, B-5 group with 5% barley grain, B-10 group with 10% barley grain. A-5 group with 5% apple and A-10 group With 10% apple. The silos were opened after 2 months of fermentation and the quality of the silages, changes in their physical aspect. fermentation products and rumen dry matter and crude protein degradability were assessed. Silages were evaluated physically: all treatments tested produced good quality silage, while the control was of average quality. Dry matter was highest in the B-10 group silage (p<0.05). Ash, Crude protein. ether extract and crude fiber were similar in the test groups and were higher than in their corresponding, fresh material (alfalfa be fore ensiling). while nitrogen free-extract levels were higher in fresh material. The highest pH wits found in the control group (p<0.05) and was not different between test groups. The lowest lactic acid level was found in the control group (p<0.05). and it was not different between test groups. NH3-N levels were similar in all the groups. In conclusion, high-sugar containing fruit. Such as apples. can be added to alfalfa silages as it carbohydrate Source. therefore ensuring adequate fermentation during the ensiling process.
Keywords: alfalfa silage; apple; barley; sucrose; silage quality